Death by intermission - Morgan, Alexis (Morgan, Alexis. Abby McCree mystery., 2021)
When murder has a starring role during the town's Movies in Park, and her mother's boyfriend is accused of the crime, Abby must launch her own investigation and shine a spotlight on the real killer.